Climate variability impact assessment on the flood risk in Slovenia. (2nd January 2016) - Šraj, Mojca; Menih, Matevž; Bezak, Nejc
Abstract: Assessment of climate change or climate variability is a significant topic in most geophysical disciplines. In this study, the flood frequency approach was selected to analyze changes in flood series. Discharge data from 55 gaging stations in Slovenia were used. The annual maximum method was applied to define the samples. The data sets were divided into 30-year periods based on a 10-year moving window. For each part of the data-set, the flood frequency analysis was performed. Changes in the estimated design discharge values with a 10-year return period, which is commonly used in engineering design, were observed for the two selected 30-year periods, namely 1961–1990 and 1981–2010, and the results were compared with the Mann–Kendall (MK) test. The results indicate that no uniform pattern can be found in the differences between estimated design discharge values for the two selected periods. The same applies to the MK trend test results, which were positive and statistically significant with the chosen significance level of 0.05 only for approximately 5% of stations. However, our comparison of the results of the flood frequency analyses among different 30-year periods showed considerable changes in the design discharge for some stations.